1987
DOI: 10.1038/bjc.1987.193
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of radiation sensitivity of human squamous carcinoma A431 cells

Abstract: Summary Studies have been performed to investigate the radiosensitivity of human squamous carcinoma cells. A431 cells were grown in itro as exponential and fed-plateau monolayer cultures or as multicellular spheroids. Radiobiological studies of various cultures showed that fed-plateau phase cells were more sensitive (Do =1.3Gy) than exponentially growing cells (Do =1.5Gy). After a single dose of 12Gy or two doses of 6 Gy irradiation, A431 cultures exhibited a large capacity for potentially lethal damage (PLD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Repopulation of tumor cells during treatment, tumor hypoxia, and resistance to radio-C therapy have all been implicated as causes of treatment failure after primary radiotherapy. [1][2][3] Accelerated fractionation irradiation, which shortens the total time of treatment, has been employed to increase the probability of locoregional control by reducing the risk of tumor repopulation. With hyperfractionated irradiation, multiple small fractions of radiation are given each day to increase the total dose but not the risk of long-term toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Repopulation of tumor cells during treatment, tumor hypoxia, and resistance to radio-C therapy have all been implicated as causes of treatment failure after primary radiotherapy. [1][2][3] Accelerated fractionation irradiation, which shortens the total time of treatment, has been employed to increase the probability of locoregional control by reducing the risk of tumor repopulation. With hyperfractionated irradiation, multiple small fractions of radiation are given each day to increase the total dose but not the risk of long-term toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that retinoic acid compounds play an important role in cell proliferation, diferentiation, and skin infammation and have a strong role in inducing diferentiation and inhibiting proliferation of tumor cells [38]. Gong [39] showed that combined application of retinoic acid and TNF-α can activate the expression of Caspase-3 protein, increase the expression of Caspase-3, and promote the apoptosis of human epidermal squamous cell carcinoma cell A431, which is a feasible way to treat squamous cell carcinoma. Pubescenol is a lactone.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vivo and ex vivo analysis revealed that the tumor line responded to the single high dose fraction of radiation. A 10 Gy dose was chosen based on an earlier study characterizing the radiation sensitivity of human squamous carcinoma A431 cells 26 . The use of in vivo CELI to track the diffusive spread of phosphorescent tattoo ink as a measure of treatment response in an A431 mouse xenograft model was successful after two days.…”
Section: Discussionmentioning
confidence: 99%